Pedestrian mobility for individuals with disabilities: The case of Bole, Ambo town, West Shoa Zone, Ethiopia. - Itefa, Edebusa (ASTU, 2021)
Disability is the consequence of an impairment that may be physical, cognitive, mental, sensory, emotional, developmental, or some combination of these that result in restrictions on an individual's ability to participate in what is considered "normal" in their everyday society. A disability may be present from birth, or occur during a person's lifetime. Many people with disabilities do not have equal access to health care, education, and employment opportunities, they do not receive the disability-related services that they require, and experience exclusion from everyday life activities. In addition, it helped to bring together the empirical evidence on the nature and type of the problems of the transportation of People with Disabilities and to develop policy-relevant data on disability as well as to add necessary data to the pool of existing policies to be used by policymakers in designing safe sidewalk pedestrian mobility systems that serve everyone equally. The study was conducted in Ambo town using both qualitative and quantitative research (Mixed Approach) using different instruments. The purpose of this study was to assess the safe sidewalk pedestrian mobility for disables in Ambo town; specifically Bole local places. Both explanatory approaches and descriptive research method were applied. Participants of the research was selected randomly using small population size sampling method, and from the selected sample first hand data collected through questionnaires, semi structured interview, focus group discussion and observation. Secondary data were collected from published and unpublished, hard and soft copy documents. After collecting primary and secondary data, both qualitative and quantitative data analysis methods were used to analyze the data and presented in tables, figures and in text forms. The researcher has found and concluded that the pedestrian mobility system for disabled people in Ethiopia is inaccessible and the causes for inaccessibility are lack of infrastructure provision, environmental barrier, and lack of public awareness, poor design of flow entities or safe pedestrian mobility, are identified as causes for pedestrian free mobility system problem for disabled people. Moreover, Ambo transport policy were limited emphasis for disable and the policy is not implemented. Finally, the researchers recommend that infrastructure should be accessible, and safe, the vehicle design should be accommodative and the government should implement the international agreements related with disables. More over the policy should be revised and participatory.
Keywords: Disables, Pedestrian, Policy, People with Disability, and Transport.